PENGARUH PROFESIONALISME DAN GURU SERTA MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 1 KRADENAN - Titik Rahayu (JI@P, 2015)
Titik Rahayu. 2015. “Effect of teacher professionalism, teacher performanceand student learning motivation toward the student learning achievement inState High School I (SMA Negeri 1) Kradenan. Slamet Riyadi University,Surakarta, Thesis, unpublished.This research aimed to find out (1) the effect of teacher professionalism onstudents’ learning achievement, (2) the effect of teacher performance onstudents’ learning motivation, (3) the effect of students’ learning motivationon learning achievement, and (4) the effect of teacher professionalism,teacher performance and students’ learning motivation on students’ learningachievement. The sample of research consisted of the graders of XI.IPA 1-3and XI.IPS 1-3 of SMA N 1 Kradenan, containing 60 respondents. Technique ofcollecting data used questionnaire through validity, reliability, and normalitytests. Technique of analyzing data used was path analysis, the combination ofcorrelation and regression, including product moment correlational, F- andmultiple regression tests. Research result indicated that (1) There is asignificant effect of teacher professionalism on students’ learningachievement, indicated by the correlation coefficient of 0.324 (low level ofrelationship) and p < 0.05. (2) There was a significant effect of teacherprofessionalism on students’ learning motivation, indicated by the correlationcoefficient of 0.317 (low level of relationship) and p < 0.05. (3) There was asignificant effect of teacher performance on students’ learning motivation,indicated by the correlation coefficient of 0.456 (medium level of relationship)and p < 0.05. (4) There was a significant effect of teacher performance onstudents’ learning achievement, indicated by the correlational coefficient of0.314 (low level of relationship) and p < 0.05. (5) There was a significant effectof students’ learning motivation on learning achievement, indicated by thecorrelational coefficient of 0.643 (high level of relationship) and p < 0.05. (6)There was a significant effect of teacher professionalism, teacherperformance and students’ learning motivation simultaneously towardstudents’ learning achievement, indicated by the multiple correlationcoefficient of 0.655 (high level of relationship) and p < 0.05. To improve thestudents’ learning achievement in SMA N 1 Kradenan, the students’ learningmotivation should be improved supported by the improvement of teacher’sperformance and professionalism.Keywords: teacher professionalism, teacher performance, student learningmotivation, student learning achievement.